THE USE OF HYDROGEOPHYSICAL CHARACTERISTICS WHEN SCHEMATIZING THE GEOFILTRATION CONDITIONS OF VOLCANIC REGIONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
In volcanic rocks of aquiferous effusive complex, lithogeneticcraks sharply prevail over cracks of tectonic and exogenous origins. In fact, in lava rocks blocking is completely due to lotogenetic cracks. The presence of fractured zones in lava rocks casuses electrical anisotropy that is unequal electrical conductivity in different directions. This factor allows in favorable conditions to use circular vertical electrical sensing to determine the dominant direction of the fractured zones and changes in their intensity at various depths. Within quasi homogeneous, in mineral compositions lava formation in a saturated state, the relative electrical resistance is closely related to their porosity and fracture.
Keywords: craks; lava rocks; the grandwater; hydro geophysical method; electrical conductivity; apparent resistance; filtration coefficient; correlation relationship